2014
DOI: 10.1159/000365389
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Morphometric Characteristics of Nonsyndromic Cleft Lip and Palate

Abstract: Nonsyndromic cleft lip and palate (NSCLP) encompasses a group of orofacial abnormalities. Emerging evidence has revealed the presence of structural brain abnormalities in affected individuals. Previous studies have performed structure-based volumetric analysis of the brain assessing gross lobular subdivisions of the cerebral cortex and white matter which may have only vague relationships to the functional subregions implicated in behavioral and cognitive deficits observed in NSCLP patients. High-resolution mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…31 Interestingly, associations between nonsyndromic OFC and structural brain anomalies have been reported in children and adolescents with clefts. 32,33 These midline brain anomalies have been associated with intellectual disability, developmental delay, and schizophrenia in previous studies. 34,35 The relatively high incidence of central nervous system abnormalities among individuals with nonsyndromic OFC, being approximately 13 times higher compared to that in the general population, 36 provides additional support for the hypothesis that cognitive and language deficits as well as other psychiatric disorders may be the result of underlying neurodevelopmental abnormalities.…”
Section: Discussionmentioning
confidence: 81%
“…31 Interestingly, associations between nonsyndromic OFC and structural brain anomalies have been reported in children and adolescents with clefts. 32,33 These midline brain anomalies have been associated with intellectual disability, developmental delay, and schizophrenia in previous studies. 34,35 The relatively high incidence of central nervous system abnormalities among individuals with nonsyndromic OFC, being approximately 13 times higher compared to that in the general population, 36 provides additional support for the hypothesis that cognitive and language deficits as well as other psychiatric disorders may be the result of underlying neurodevelopmental abnormalities.…”
Section: Discussionmentioning
confidence: 81%
“…An emerging alternative hypothesis holds that OFC-associated adverse neurobehavioral outcomes stem from primary neuroanatomical abnormalities related to cleft pathogenesis itself. In addition to the well-described interdependence of face and brain development 18 , this hypothesis is supported by recent neuroimaging studies documenting subtle and partially overlapping structural brain anomalies in patients born with OFCs 19 23 , in fetal mice with OFCs 24 , and adult mice with OFC-associated mutations 25 .…”
Section: Introductionmentioning
confidence: 71%
“…Compared with control (PoCG; P<0.001, uncorrected) and aNSCLP groups (P<0.05, cluster-level FWEcorrected), the bNSCLP group had an increased GMV in left postcentral gyrus. A previous study has demonstrated increased GMV in bilateral PoCG in children with NSCLP [ 8 ], indicating that this is an important region in the NSCLP cohorts. A previous analysis of stuttering adults has found increased GMV in the precentral and postcentral gyrus, inferior parietal, and temporal lobule of bilateral hemisphere, which might represent a long-term functional compensation for the cerebella and medulla function deficiency [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brain morphological analyses of NSCL/P adults have indicated brain changes, such as increased frontal lobe volumes, decreased temporal and occipital lobe volumes, lower cerebellum volumes, and higher rates of cavum septum pellucidum compared with normal controls [ 11 14 ]. A pediatric NSCL/P study has found that compared with age-matched controls, children with NSCL/P (6 to 14 years of age) have increased global cortical gray matter volumes (GMV) with decreased volumes of subcortical grey matter and cerebral white matter structures [ 8 ]. Besides, they have increased cortical thickness (CT) in left frontal and right parietal lobes and decreased CT in right superior frontal cortex [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation